Integrating Risk Intelligence into Defense Policy: A Strategic Risk Management Approach - Sarjito, Aris (Jurnal Ilmu Sosial dan Humaniora, 2024)
The increasing complexity and unpredictability of global threats, including cyberattacks and hybrid warfare, necessitate the integration of risk intelligence into defense policy frameworks. Risk intelligence, a proactive tool for anticipating and mitigating risks, plays a crucial role in enhancing situational awareness, resource optimization, and decision-making in defense strategies. This research aims to explore the integration of risk intelligence into defense policies through a strategic risk management approach, highlighting its importance, challenges, and practical implementation. A qualitative methodology was adopted, utilizing secondary data from government policy documents, international defense reports, and scholarly articles. Findings reveal that while risk intelligence enhances preparedness and adaptability in defense policies, its implementation faces barriers such as technological limitations, data silos, and resistance to change. Enablers include advancements in artificial intelligence, inter-agency collaboration, and structured policy frameworks. The study concludes that integrating risk intelligence into defense policies requires establishing dedicated units, investing in technology and training, and fostering international partnerships to share intelligence. These measures can bridge existing gaps, ensuring defense policies are resilient and proactive in managing contemporary and emerging threats. Keywords : cybersecurity, defense policy, hybrid threats, risk intelligence, strategic risk management